Promoting Psycho-Social-Spiritual Response in Patients with Type 2 Diabetes Mellitus through Aplication on Self Care Management Modul - Kusnanto Kusnanto (Universitas Airlangga, 2013)
Introduction: Diabetes mellitus was a kind of incurable chronic disease that actually manageable. The global prevalence tends to increase due to less self management of the disease and the impact of it was severe health condition. There were so many interventions implemented but failed to give optimal improvement in patient’s condition and there are so many DM patients have insufficient ability to manage their own disease. Patients need to have knowledge, skills, and self confident to be able to manage their disease. Patient’s self-management depends on patient’s education, empowerment, and self monitoring in evaluating their self-care management. The purpose of this research was promoting patient’s psychological, social, and spiritual conditions through Self Care Management. Improvement in psychological, social, and spiritual conditions in patients with DM will lead to better level of blood glucose and HbA1C.Methods: Patient newly diagnose with Type 2 DM at Puskesmas Kebonsari was selected with purposive sampling and divided into two groups. Each group contains 25 patients. Intervention group was given Self Diabetes Management Module. Before and after intervention patient was given Questionnaire. The data then analyzed using Student-T test, McNemar and Chi-Square.Results: The result of this research showed patient have constructive coping, increase interpersonal relation. Patients also have better acceptance about the disease and involve in its management.Conclusion: Self Care Management Module promotes psychological, social, and spiritual conditions in patients with type 2 DM.